Feeding Ecology of Invasive Three-Spined Stickleback (Gasterosteus aculeatus) in Relation to Native Juvenile Eurasian Perch (Perca fluviatilis) in the Pelagic Zone of Upper Lake Constance - Bretzel, Joachim Benedikt; Geist, Juergen; Gugele, Sarah Maria; Baer, Jan; Brinker, Alexander (Frontiers in Environmental Science, 2021)
The fish community of Lake Constance, a large, deep, oligotrophic lake has undergone drastic changes in recent years, with the sudden rise to dominance of invasive three-spined stickleback (Gasterosteus aculeatus) in the pelagic zone, a rather atypical habitat for this species in Central Europe. The core objective of this study was to compare the feeding ecology of stickleback and young Eurasian perch (Perca fluviatilis) in this unique situation to identify reasons for this unexpected dominance, a possible food niche and feeding time overlap, and to discuss consequences for the reshaped pelagic fish community. The diel feeding patterns and prey compositions of pelagic sticklebacks and juvenile (0+) perch sampled in October 2018 and March 2019 were studied analyzing stomach contents. The diets of both species mostly comprised zooplankton, with copepods appearing in the greatest numbers. Benthic and airborne insects were consumed occasionally, mostly by sticklebacks. Both species exhibited peaks of feeding activity early in the morning, afternoon and dusk, and in both species, stomachs were fullest at dusk. Stickleback stomachs contained about 20% more prey at night than perch, and mean estimated nocturnal stomach fullness values were almost 50% greater. Night feeding in sticklebacks was confirmed by digestive states, pointing to a possible competitive advantage over perch. Dietary composition varied over a 24-h cycle and the pattern of consumption of different prey varied between the species. Perch consumed more comparatively small cladocerans (Bosmina spp.), while larger Daphnia appeared more often in stickleback stomachs. In both species, seasonal variation in diet mirrored food availability, indicating some degree of opportunism. A Morisita-Horn index value of 0.95 confirmed dietary niche overlap between species, suggesting the large population of sticklebacks may exert a competitive effect on juvenile perch when resources are limited. Both the longer feeding periods and greater intake of nutritive high quality prey like daphnids can contribute to the rapid success of stickleback in dominating the pelagic zone of Lake Constance.